1983
DOI: 10.1128/aac.23.4.515
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between antifungal activity and inhibition of sterol biosynthesis in miconazole, clotrimazole, and 15-azasterol

Abstract: The availability of Saccharomyces cerevisiae mutants which are defective in sterol biosynthesis makes it possible to determine whether the ability of several antifungal agents to inhibit cell growth is due to their effect on sterol production. 15-Aza-24-methylene-8,14-cholestadien-3 beta-ol (15-azasterol) is known to block the reduction of the sterol delta 14 bond following C-14 demethylation. This agent inhibits the growth of wild-type S. cerevisiae but does not inhibit the growth of a strain that is defectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1
1

Year Published

1986
1986
2008
2008

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 32 publications
0
11
1
1
Order By: Relevance
“…Scott et al (259) demonstrated a reduction in ergosterol levels in T. mentagrophytes following exposure to miconazole as well. In contrast, Taylor et al (299) have presented data indicating that inhibition of C-14 demethylation is not a fungicidal event. They have proposed that direct membrane damage to the fungus may be the key antifungal activity of miconazole and other imidazole drugs.…”
Section: Clotrimazolementioning
confidence: 88%
“…Scott et al (259) demonstrated a reduction in ergosterol levels in T. mentagrophytes following exposure to miconazole as well. In contrast, Taylor et al (299) have presented data indicating that inhibition of C-14 demethylation is not a fungicidal event. They have proposed that direct membrane damage to the fungus may be the key antifungal activity of miconazole and other imidazole drugs.…”
Section: Clotrimazolementioning
confidence: 88%
“…This idea is supported by several previous observations and comments. Taylor et al (14) showed that the azoles were still inhibitory toward sterol auxotrophic mutants of S. cerevisiae. Odds (11) also states, "most azoles are able to prevent or greatly perturb hyphal growth of C. albicans.…”
mentioning
confidence: 99%
“…If growth inhibition were simply due to the depletion of ergosterol, strain JR4 would be as susceptible or perhaps more susceptible to fenpropimorph than the wild-type strain is. It has been demonstrated that 14-methylfecosterol can satisfy the bulk membrane requirements, but not the structurally specific sparking function, which can be fulfilled by the small amounts of ergosterol that are produced (19,21).…”
Section: Fp13c (Fen] Fen2 Leu2 Ura3 His4) and Fp13d (Fen] Fen2mentioning
confidence: 99%
“…Studies with S. cerevisiae have demonstrated that 15-azasterol inhibits the A' isomerase and C-14-reductase of the ergosterol pathway, similar to fenpropimorph, which results in the production of ignosterol (7). Thus, it was of interest to It has been shown previously (21) that strain JR4 (erg3 ergll), which carres mutations in C-5-desaturase and C-14-demethylase, respectively, is resistant to the growth inhibitory effects of 15-azasterol. Because of these mutations in the sterol pathway, 14-methylfecosterol [14a-methyl-ergosta-8,24(28)-dien-3p-ol] is the major sterol produced in this strain (21).…”
Section: Fp13c (Fen] Fen2 Leu2 Ura3 His4) and Fp13d (Fen] Fen2mentioning
confidence: 99%
See 1 more Smart Citation